Pengaruh Transfer Pricing, Firm Size, Leverage, Sales Growth Terhadap Tax Avoidance dengan Profitability sebagai Variabel Moderating Pada Perusahaan Manufaktur dan Dagang Yang Terdaftar Di JII 70 Tahun 2019-2023 - Nur Isnaini; Arismaya, Anisa Dewi (Shafin: Sharia Finance and Accounting Journal, 2025)
This research is motivated by the phenomenon of tax avoidance carried out by PT Bentoel Internasional Investama in 2019 which is engaged in manufacturing. This research is a quantitative study that aims to determine the effect of transfer pricing, company size, leverage, sales growth on tax avoidance with profitability as a moderating variable in manufacturing and trading companies listed on the JII 70 years 2019-2023. with the type and source of secondary data obtained from the company's financial statements through the official website of the Indonesia Stock Exchange or the company's official website. The data analysis technique used is panel data regression analysis and MRA which is processed using E-Views 12. The results of this study indicate that transfer pricing, firm size, leverage, sales growth do not significantly affect tax avoidance. Transfer pricing, firm size, leverage, sales growth on tax avoidance cannot be moderated by profitability.